2013
DOI: 10.1182/blood-2013-06-506741
|View full text |Cite|
|
Sign up to set email alerts
|

Infusion of donor-derived CD19-redirected virus-specific T cells for B-cell malignancies relapsed after allogeneic stem cell transplant: a phase 1 study

Abstract: Key Points Allogeneic CD19-CAR VSTs are well tolerated by patients with relapsed B-cell malignancies post-HSCT. At periods of CD19-CAR VST persistence, these cells demonstrate antitumor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
379
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 464 publications
(397 citation statements)
references
References 41 publications
(66 reference statements)
10
379
2
6
Order By: Relevance
“…At the same center, two patients with B cell acute lymphoblastic leukemia (B-ALL) also achieved complete remission after CD19-specific CAR-modified autologous T cell therapy; however, one relapsed within 2 months of therapy with CD19-negative disease [59]. Other studies in which patients were treated with autologous T cells modified with CD19-specific CARs that incorporated costimulatory domains derived from CD28 have also demonstrated anti-tumor effects in patients with B cell malignancies [8,54,56,57]. Remarkable efficacy was seen after treatment of 5 B-ALL patients at Memorial Sloan Kettering Cancer Center with lymphodepleting chemotherapy and T cells modified to express a CD19-specific CAR incorporating a CD28 costimulatory domain [8].…”
Section: Clinical Trialsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the same center, two patients with B cell acute lymphoblastic leukemia (B-ALL) also achieved complete remission after CD19-specific CAR-modified autologous T cell therapy; however, one relapsed within 2 months of therapy with CD19-negative disease [59]. Other studies in which patients were treated with autologous T cells modified with CD19-specific CARs that incorporated costimulatory domains derived from CD28 have also demonstrated anti-tumor effects in patients with B cell malignancies [8,54,56,57]. Remarkable efficacy was seen after treatment of 5 B-ALL patients at Memorial Sloan Kettering Cancer Center with lymphodepleting chemotherapy and T cells modified to express a CD19-specific CAR incorporating a CD28 costimulatory domain [8].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Remarkable efficacy was seen after treatment of 5 B-ALL patients at Memorial Sloan Kettering Cancer Center with lymphodepleting chemotherapy and T cells modified to express a CD19-specific CAR incorporating a CD28 costimulatory domain [8]. Two recent reports have suggested that CD19-specific CAR-modified T cell therapy may have anti-tumor activity in allogeneic hematopoietic stem cell transplant (HCT) recipients [54,60]. The concern that administration of allogeneic CAR-modified T cells that express endogenous potentially alloreactive TCRs could exacerbate graft versus host disease (GVHD) stimulated development of strategies to CAR-modify virus-specific T cells, which have been shown to have a lower risk of causing GVHD after adoptive transfer [13,54,61].…”
Section: Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The induction of lasting remissions makes the CD19 targeting CAR T cell trial [3] a milestone in the CAR field, although the trial at University of Pennsylvania is not the first or the only CAR T cell study to be launched in humans. Other centers including Sloan Kettering Memorial Institute successfully treated chronic lymphatic leukemia patients with anti-CD19 CAR T cells as well [4,5]. Of even stronger public perception was one of the follow-up trials targeting pediatric acute lymphoblastic leukemia (ALL) with CTL019 in 2012, when the first treated patient went into complete and lasting remission, and which was rewarded as 'Breakthrough Therapy' for relapsed and refractory ALL in adults and children by the US FDA in 2014.…”
mentioning
confidence: 99%